EVALUATION OF THE MOLLUSCICIDAL POTENTIAL OF HYDROALCOHOLIC EXTRACTS OF Jatropha gossypiifolia Linnaeus, 1753 ON Biomphalaria glabrata (Say, 1818) - Pereira Filho, Adalberto Alves; França, Clícia Rosane Costa; Oliveira, Dorlam's da Silva; Mendes, Renato Juvino de Aragão; Gonçalves, José de Ribamar Santos; Rosa, Ivone Garros (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The action of extracts from the stem, leaves, and fruit of Jatropha gossypiifolia on Biomphalaria glabrata was studied by analyzing survival, feeding capacity and oviposition ability. The extracts were obtained by macerating the plant parts in 92% ethanol, which were then evaporated until a dry residue was obtained and phytochemically studied. The molluscicidal activity on B. glabrata was investigated using the procedures recommended by WHO (1965). The amount of food ingested and oviposition were measured during each experiment. The extract of leaves from J. gossypiifolia was shown to be a strong molluscicidal agent, causing 100% mortality of B. glabrata, even in the lowest concentration tested, of 25 ppm. Regarding the fruit extract, there was variation in the mortality, depending on the concentration used (100, 75, 50 and 25 ppm). The snails that were in contact with the fruit extract had significant reduction in feeding and number of embryos in comparison to the control. The stem extract did not present molluscicidal activity nor had any influence on the feeding and oviposition abilities of B. glabrata, in the concentrations tested. In conclusion, the extracts of leaves and fruits of J. gossypiifolia investigated in this work show molluscicidal effect and may be sources of useful compounds for the schistosomiasis control.